Entrepreneurial motivation factors, management strategies, and challenges : a case study of Kuching women micro and small business owners - Uchenna, Okpara Izuagba (Universiti Malaysia Sarawak, (UNIMAS), 2014)
(This study examined the factors that motivated Malaysian women entrepreneurs, specifically those who operate in Kuching, Sarawak, to start-up their own businesses. However, the core focus of this study is on women entrepreneurs that are categorized as owners of `micro and small enterprises (MSEs)'. This study also assessed the management strategies practiced by these women and the effects of these strategies on their businesses. In addition, it explored the challenges they are facing and the effects of these challenges on their businessel Mixed method approach and non-probability sampling method, specifically purposive sampling was used to conduct this study. The instruments that were used to gather primary data are questionnaires and interviews; 300 respondents were involved in this study, 269 of them were given questionnaires, while 31 of them were interviewed. Out of the 269 respondents that were given questionnaires, 252 of them returned theirs, while 17 of them failed to do so. This means that a total of 283 respondents provided the primary data that was used to conduct this study. The findings of this study showed that 90.5% of the respondents that were given questionnaires will consider their businesses as successful ventures whenever their sales and/or profits begin to increase, while 9.5% of them will consider theirs as successful whenever they are able to expand. Similarly, 32.3% of those interviewed mentioned that they will consider their businesses as successful ventures when they are able to expand, while 67.7% of them mentioned that they will consider theirs as successful when their sales and/or profits start to increase. The findings also showed that the respondents were motivated to start-up their own businesses by various extrinsic and intrinsic motivation factors. The major extrinsic motivation factors that encouraged them to start-up their own businesses are `their low educational background' and `the opportunity to manage their time by themselves'. On the other hand, the major intrinsic motivation factor that encouraged the respondents to start-up their own businesses is `to become their own boss'. The findings equally showed that there is a positive and significant correlation between extrinsic motivation factors and sales and profit satisfaction. On the contrary, it also showed that there is a negative and significant correlation between intrinsic motivation factors and sales and profit satisfactions. Additionally, it was found that the management strategies used by respondents in the retail and service sectors are the same, but they apply them in different ways. Out of the seven strategies examined in this study, the findings showed that the respondents use five of them to manage their businesses, this includes; differentiation, focus, product or service development, market development, and market penetration. The findings also showed that the respondents do not use the remaining two strategies, which include cost leadership and diversification, due to the size and nature of their businesses. It was equally found that the five strategies used by the respondents do not only help to increase their market shares and profits, they also help them to expand their businesses. Moreover, it was found that two of the challenges examined in this study are only faced by respondents in the service sector, this includes; 'inadequate training' and the inability to employ skilful workers'. On the other hand, other challenges examined are faced by respondents in both the retail and service sectors. The findings showed that almost all the respondents (90.3%) in both the retail and service sectors consider `intense competition from small and large companies' as the biggest challenge they are facing in their businesses. However, it was equally found that these challenges are negatively affecting their businesses.